Easily adhesive polyamide film and manufacturing method thereof

By using specific polyurethane resin and biaxial stretching technology in the primer of the polyamide film, the problem of deterioration of adhesion and adhesion of the polyamide film after hot water treatment is solved, and high adhesion, excellent processing performance and printing appearance are achieved.

CN119866271APending Publication Date: 2025-04-22UNITIKA LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380068417.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-06
Filing Date
2023-09-26
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The adhesion of existing polyamide films decreases after hot water treatment and is prone to adhesion, which affects the processing performance and printing appearance.

Method used

In the undercoat layer of the polyamide film, polyurethane resin A without silanol group and polyurethane resin B with silanol group are used, and excellent adhesiveness is formed by biaxial stretching and heat treatment.

Benefits of technology

It achieves high adhesion and excellent adhesion resistance, printing suitability and transparency after hot water treatment, and is suitable for packaging materials and food packaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119866271A_ABST
    Figure CN119866271A_ABST
Patent Text Reader

Abstract

The present invention addresses the problem of providing a highly adhesive polyamide film having high adhesion even after hot water treatment, and also having excellent blocking resistance, printability, transparency, and the like. [Solution] The present invention relates to a highly adhesive polyamide film in which an undercoat layer is formed on at least one surface of a polyamide base film, and is characterized in that: (1) the undercoat layer contains a urethane resin (A) that does not have a silanol group and a urethane resin (B) that has a silanol group; (2) The glass transition temperatures (Tg) of the polyurethane resin A and the polyurethane resin B are different from each other.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a novel easy-adhesion polyamide film and a method for producing the same, and in particular to an easy-adhesion polyamide film suitable for use in packaging materials, electrical insulating materials, general industrial materials, etc. and a method for producing the same. Background Art

[0002] In addition to excellent mechanical properties, optical properties, thermal properties, barrier properties, etc., biaxially stretched polyamide films are also excellent in abrasion resistance, impact resistance, pinhole resistance, etc., and are therefore widely used as films for packaging food and other items. In these applications, various secondary processes are usually applied to the surface of the substrate film, such as coating processes of various coating agents, printing processes, vapor deposition processes, and lamination processes with other films. Therefore, attempts have been made to modify the surface of the substrate film by applying physical surface treatments such as corona discharge treatment and plasma treatment to the substrate film, or applying chemical surface treatments such as acids and alkalis to activate the film surface, thereby improving the adhesion between the substrate film and the covering body obtained by the secondary processing.

[0003] However, although the process of physical surface treatment is relatively simple, the obtained adhesion is insufficient, while the process of chemical surface treatment is not only complicated, but also has problems such as deterioration of the working environment.

[0004] When polyamide films are used for food packaging, a method of laminating a sealing film after printing is generally adopted as needed. However, if the adhesion between the two films is weak, the polyamide film as a base material and the sealing film may peel off (so-called delamination phenomenon) when boiling treatment or retorting treatment is performed for sterilizing the contents.

[0005] In order to solve this problem, in addition to the above-mentioned physical or chemical surface treatment methods, there is another method of applying a primer having adhesive activity to the substrate film to form an easy-adhesion coating film (hereinafter referred to as "primer coating"). This method is widely used because the primer components can be selected according to various surface coatings.

[0006] As a constituent component of the primer layer, water-based resins are often used from the perspectives of workability, safety, and cost. Among them, polyurethane resins, polyester resins, acrylic resins, etc. are particularly used to improve adhesion with a coating layer, ink layer, vapor-deposited layer, etc., which are the top coat layers (Patent Documents 1 to 7).

[0007] Among them, it is known that, for example, by controlling the thickness of the primer layer of the easy-adhesive polyamide film, the physical properties of the polyurethane resin used as the easy-adhesive coating agent, and the amount of the volatile alkali component remaining in the primer layer, the surface characteristics of the coating film are improved, and the method of improving the adhesion after hot water treatment is used (Patent Document 7). According to Patent Document 7, for the volatile alkali component, by making the primer layer not contain a curing agent (cross-linking agent), the total amount of the volatile alkali component can be reduced, and the decline in water resistance can also be suppressed. In addition, safety can also be improved when used in packaging materials for food.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent Application Laid-Open No. 2022-38956

[0011] Patent Document 2: Japanese Patent Application Laid-Open No. 2020-121496

[0012] Patent Document 3: Japanese Patent Application Laid-Open No. 2014-22080

[0013] Patent Document 4: Japanese Patent Application Laid-Open No. 2000-26798

[0014] Patent Document 5: Japanese Patent Publication No. 3-55302

[0015] Patent Document 6: International Publication No. WO2008 / 75461

[0016] Patent Document 7: International Publication No. WO2010 / 110282 Summary of the invention

[0017] Problem that the invention aims to solve

[0018] However, in these conventional films, further improvement is needed in terms of so-called blocking resistance. That is, when operating the film in the form of a roll, the phenomenon of "blocking" in which the films stick to each other will occur easily. In particular, as disclosed in patent documentation 7, when curing agent is not contained in the primer, the phenomenon will have a significant trend. In addition, when corona discharge treatment is implemented on the face opposite to the primer for the intermediate layer of the multi-layer laminated laminate, it will become easier to produce blocking and easily cause processing failure. At this time, although there is a method of adding a lubricant in the primer in order to suppress blocking, if a large amount of lubricants are added, the mist will rise, and there will be a risk of damaging transparency and reducing printing visibility.

[0019] In addition, in the previous films, there is still room for improvement in the printability caused by the primer layer. In product packaging, in addition to environmental publicity, various printings are applied as a way to express personality, and the requirements for printed appearance are also tending to be higher. In this regard, there is also the following problem: the localized reduction of printed appearance due to the coating characteristics of the primer layer used in the previous films, and there is also room for improvement in this regard.

[0020] In recent years, with the aging of consumers and the diversification of products, the demand for long-term storage of food packaging has become higher, and the need for hot water boiling treatment in the sterilization / sterilization process has also increased. In addition, since boiling treatment may also be applied in a gas-containing state, it is also required to maintain high lamination strength under more severe environments.

[0021] Thus, it is necessary to develop a material that can maintain high adhesion even after hot water treatment such as boiling or retorting and that is excellent in blocking resistance, printability, transparency, etc., and conventional films still have room for further improvement in these aspects.

[0022] Therefore, a main object of the present invention is to provide an easily adhesive polyamide film which has high adhesion even after hot water treatment and is excellent in blocking resistance, printability, transparency, etc.

[0023] Means for solving problems

[0024] The present inventors have conducted intensive studies in view of the problems of the prior art and, as a result, have found that the above-mentioned object can be achieved by forming a primer layer containing a specific component on a polyamide film, thereby completing the present invention.

[0025] That is, the present invention relates to the following easily adhesive polyamide film and a method for producing the same.

[0026] 1. An easy-adhesion polyamide film, characterized in that it is a polyamide film having a primer layer formed on at least one surface of a polyamide substrate film, and

[0027] (1) the primer layer comprises a polyurethane resin A having no silanol group and a polyurethane resin B having a silanol group,

[0028] (2) The polyurethane resin A and the polyurethane resin B have different glass transition temperatures (Tg).

[0029] 2. The easily adhesive polyamide film according to item 1 above, wherein the glass transition temperature (Tg) of the polyurethane resin A is in the range of 5 to 50°C, and the glass transition temperature (Tg) of the polyurethane resin B is in the range of 60°C or higher.

[0030] 3. The easily adhesive polyamide film according to the above item 1, wherein the polyurethane resin A accounts for 25 to 80 parts by mass and the polyurethane B accounts for 20 to 75 parts by mass, based on 100 parts by mass of the total of the polyurethane resin A and the polyurethane resin B.

[0031] 4. The easily adhesive polyamide film according to item 1 above, wherein the polyurethane resin A has a film elongation of 300% or more and a tensile strength of 20 to 50 MPa, and the polyurethane resin B has a film elongation of 200% or more and a tensile strength of 40 to 60 MPa.

[0032] 5. The easy-adhesion polyamide film as described in the above item 1, wherein the 2.5 mm thick 50% gradation portion of the halftone printing printed on the above primer layer 2 The area of ​​300 dots within the printed film is measured in length at any 10 locations in the TD direction, and the minimum to maximum area ratio (average value of the 20 dots with the smallest area / average value of the 20 dots with the largest area) is in the range of 0.8 to 1.

[0033] 6. The easily adhesive polyamide film as described in the above item 1, wherein the adhesion after the primer layers are superimposed on each other and a load of 10 kg / cm is applied and the film is placed in an environment of 40° C. for one week is 40 g / 15 mm or less.

[0034] 7. The easily adhesive polyamide film as described in the above item 1, which has a haze of 8% or less.

[0035] 8. The easily adhesive polyamide film as described in the above item 1, which is a biaxially stretched film.

[0036] 9. A laminated body comprising at least a laminated adhesive layer and a heat seal layer laminated in this order directly or via a printed layer on the primer layer of the easily adhesive polyamide film according to any one of Items 1 to 8 above.

[0037] 10. A method for producing an easy-to-bond polyamide film, comprising:

[0038] (1) a step of applying an aqueous coating agent comprising a polyurethane resin A having no silanol group and a polyurethane resin B having a silanol group onto at least one surface of an unstretched polyamide substrate film; and

[0039] (2) A step of biaxially stretching the polyamide film coated with the aqueous coating agent and then performing a heat treatment.

[0040] 11. The production method according to the above item 10, wherein the biaxial stretching is simultaneous biaxial stretching.

[0041] 12. A method for producing an easy-to-bond polyamide film, comprising:

[0042] (1) a step of uniaxially stretching an unstretched polyamide substrate film in a first direction;

[0043] (2) a step of applying an aqueous coating agent comprising a polyurethane resin A having no silanol group and a polyurethane resin B having a silanol group onto at least one surface of a uniaxially stretched polyamide substrate film; and

[0044] (3) A step of uniaxially stretching the polyamide base film coated with the aqueous coating agent in a second direction perpendicular to the first direction and then heat treating the polyamide base film.

[0045] Effects of the Invention

[0046] According to the present invention, there can be provided an easily adhesive polyamide film which has high adhesion even after hot water treatment and is excellent in blocking resistance, printability, transparency, and the like.

[0047] Particularly, the easy-to-bond polyamide film of the present invention can achieve the same or higher adhesion (laminate strength) as before the treatment, and can also provide a film with high transparency, because the film uses two specific polyurethane resins with different glass transition temperatures in the primer layer, even after hot water treatment. As a result, the film can be provided with high transparency, because the content of lubricants can be reduced. In addition, at the same time, even after hot water treatment such as boiling treatment and steaming treatment, excellent adhesion can be maintained.

[0048] About the mechanism of action brought by using the above-mentioned two kinds of polyurethane resins, although it is uncertain, it is speculated that by using the polyurethane resin B with silanol group, and in the drying and stretching process of the film, the silanol groups react with each other to form a cross-linked structure, and the primer layer can be cured even without a curing agent, and the blocking resistance can be improved as a result. On the other hand, although the polyurethane resin A without silanol group does not form a cross-linked structure as described above, it can play the function of maintaining the affinity with the polyurethane resin B and improving the printability in the primer layer. In this way, it is believed that by using two kinds of polyurethane resins together, even after hot water treatment, high adhesion can be still provided, and excellent blocking resistance, printability, etc. can be played at the same time.

[0049] The easily adhesive polyamide film of the present invention having such characteristics can be suitably used as, for example, packaging materials, electrical insulating materials, general industrial materials, etc. In particular, it is suitable for food packaging materials that are subjected to boiling or retorting treatment after printing on the film.

[0050] In addition, the easy-adhesion polyamide film of the present invention can be easily obtained by applying an aqueous coating agent containing a polyurethane resin on a polyamide film and drying it, and has advantages such as easy thickness control. As a result, the easy-adhesion polyamide film of the present invention has excellent productivity and is also industrially advantageous.

[0051] According to the manufacturing method of the present invention, by incorporating the following process in the film manufacturing process, i.e., the process of forming the primer layer by applying an aqueous coating agent, the coating agent can be dried simultaneously in the heat treatment process with the heat setting of the polyamide film as the purpose, so the simplification of the process can be achieved. In addition, the temperature condition of the heat treatment process can be set to a higher temperature than the heating condition, and the heating condition is: the heating condition when the coating agent is applied to the film and dried after the crystallization and orientation (hereinafter also referred to as "orientation crystallization") of the molecules performed by biaxial stretching are completed. Therefore, it is conducive to reducing the volatile alkali component in the primer layer. In contrast, when a curing agent is added separately to the aqueous coating agent, a network-like cross-linked structure will be generated when drying in the production line, and the unevenness locally generated in the primer layer with the curing point as the starting point will cause the deterioration of the printed appearance. In addition, in the primer layer, if only a polyurethane resin without a curing agent is used, when it is stored in a roll after film making, adhesion will be easily generated due to changes over time. According to the present invention, by containing a silanol group-containing polyurethane at a specific blending ratio, it is possible to achieve both improvement in water-resistant adhesion and improvement in printed appearance without impairing adhesion. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 This is a diagram showing an example of the layer structure of the easily adhesive polyamide film of the present invention.

[0053] Figure 2 This is a diagram showing an example of the layer structure of the laminate of the present invention.

[0054] Figure 3 This is a diagram showing an outline of a method for evaluating the printability of a film in Test Example 1. DETAILED DESCRIPTION

[0055] 1. Easy to bond polyamide film

[0056] The easy-adhesion polyamide film of the present invention (the film of the present invention) is characterized in that it is a polyamide film having a primer layer formed on at least one surface of a polyamide substrate film, and

[0057] (1) The primer layer comprises a polyurethane resin A having no silanol group and a polyurethane resin B having a silanol group;

[0058] (2) The polyurethane resin A and the polyurethane resin B have different glass transition temperatures (Tg).

[0059] It should be noted that in the present invention, a film having a primer layer formed on at least one side of a polyamide substrate film and having no other layers laminated thereon is referred to as a "film of the present invention", and a film having other layers laminated on one or both sides of the film of the present invention is referred to as a "laminated body".

[0060] The basic layer structure of the film of the present invention is shown in Figure 1 . Figure 1 Film 10 of A has a primer layer 12 formed on one surface of a polyamide base film 11. Figure 1 In A, the primer layer 12 is formed on the entire surface of one surface of the polyamide base film 11, but may be formed on a part thereof as long as the effect of the present invention is not impaired. Figure 1 Film 10' of B has primer layer 12 formed on both surfaces (front and back) of polyamide substrate film 11. Figure 1 In B, the primer layer 12 is formed on the entire surfaces of both surfaces of the polyamide base film 11, but may be formed on a portion of the surface as long as the effect of the present invention is not impaired.

[0061] exist Figure 1 A and Figure 1 B In any case, a transparent film can be suitably used as the polyamide substrate film 11. Similarly, it is also desirable that the primer layer 12 is transparent. By constituting the film of the present invention with these transparent layers, the haze value shown below can be reliably achieved.

[0062] Polyamide substrate film

[0063] The polyamide substrate film contains a polyamide resin as a main component, and functions as a core layer of the film of the present invention or a laminate described later.

[0064] As polyamide resin, for example, nylon 6 obtained by ring-opening polymerization of raw materials containing ε-caprolactam can be cited. In addition, as other polyamide resins, polyamide resins obtained by polycondensing raw materials containing lactams with more than 3-membered rings, ω-amino acids, dibasic acids, and diamines can also be cited. The above raw materials are not limited, for example, in addition to using conventional monomers derived from petroleum, monomers obtained by depolymerization through chemical recovery can also be used.

[0065] In addition, the polyamide resin may be a remelted resin obtained by melting a polyamide resin. In the present invention, as the remelted resin, from the viewpoints of environmental protection and effective use of resources, a polyamide resin (particularly a polyamide 6 resin) may be used as a resin waste. More specifically, it may be exemplified by pellets formed by remelting unstretched scraps, ear trimming scraps, cut scraps, defective products, etc. generated during the manufacture of a polyamide film.

[0066] Specific examples of such polyamide resins include at least one of nylon 6, 7, 10, 11, 12, 4.10, 5.6, 6.6, 6.9, 6.10, 6.11, 6.12, 10.10, 6T, 9T, 10T, 6I, MXD6 (poly(meta-xylylene adipamide), 6 / 6.6, 6 / 12, 6 / 6T, 6 / 6I, and 6 / MXD6. Among them, nylon 6 having an excellent balance between heat resistance and mechanical properties is preferred.

[0067] The content of the polyamide resin in the polyamide base film is not limited, but can generally be set in the range of about 90 to 100% by mass, for example, 95 to 99% by mass.

[0068] The polyamide substrate film may contain components other than the polyamide resin within the range that does not hinder the effect of the present invention, for example, at least one of various additives such as antioxidants, ultraviolet absorbers, preservatives, antistatic agents, antiblocking agents, and inorganic fine particles.

[0069] In particular, lubricants may be mixed for the purpose of further improving the sliding property of the film. As lubricants, at least one of inorganic lubricants and organic lubricants may be used. As inorganic lubricants, for example, clay, talc, calcium carbonate, magnesium carbonate, zinc carbonate, wollastonite, silicon dioxide, aluminum oxide, calcium oxide, magnesium oxide, calcium silicate, sodium aluminate, calcium aluminate, magnesium aluminum silicate, glass hollow spheres, carbon black, zinc oxide, antimony trioxide, zeolite, hydrotalcite, layered silicate, sodium silicate, aluminum hydroxide, iron oxide, zirconium oxide, barium sulfate, titanium oxide, carbon black, etc. As organic lubricants, for example, acrylic cross-linked polymers, styrene cross-linked polymers, phenolic resins, nylon resins, polyethylene wax, ethylene bis stearamide, etc. Among these, silicon dioxide is preferred.

[0070] The content of the lubricant in the polyamide substrate film is not particularly limited, but from the viewpoint of ensuring the transparency of the film, it is preferably set to 0.5% by mass or less in the polyamide substrate film, and more preferably set to 0.3% by mass or less. The lower limit value may be set to 0.01% by mass, for example, but is not limited thereto. It should be noted that when used for purposes that do not require transparency, an amount greater than 0.5% by mass may also be blended.

[0071] The polyamide substrate film may be composed of a single layer or may be a film composed of multiple layers formed by simultaneous melt extrusion, lamination, etc. In particular, in the present invention, a polyamide substrate film composed of a single layer is preferred because it is easy to produce.

[0072] As the polyamide substrate film, a ready-made or commercially available polyamide film may be used, or a film formed by a known film-forming method may be used.

[0073] When manufacturing a polyamide substrate film, for example, after extruding a molten polymer from a T-die, it is cooled with a flow coating roll to produce an unstretched sheet. Next, it is subjected to simultaneous biaxial stretching or sequential biaxial stretching. For the stretched film thus obtained, in order to make it have good dimensional stability, a short-term heat treatment is applied at a temperature of about 200° C. This can obtain a polyamide substrate film. That is, it is desired that the polyamide substrate film in the film of the present invention is a biaxially stretched film.

[0074] Furthermore, the polyamide base film may be subjected to surface treatment such as corona discharge treatment as necessary within a range not impairing the effects of the present invention.

[0075] The thickness of the polyamide substrate film is not limited and can be appropriately set depending on, for example, the application and the site of use, but generally, it may be set within a range of about 3 to 50 μm.

[0076] Base coating

[0077] The primer layer is formed on one or both sides of the polyamide substrate film and has the function of imparting excellent adhesion to the polyamide substrate film. The primer layer of the film of the present invention comprises a polyurethane resin A without a silanol group and a polyurethane resin B with a silanol group. By containing the polyurethane resin A and the polyurethane resin B in the primer layer, the lamination strength after hot water treatment that cannot be achieved by the polyurethane resin A alone or the polyurethane resin B alone can be achieved, and good blocking resistance, printability, etc. can also be obtained.

[0078] Polyurethane resin A

[0079] The polyurethane resin A may be obtained by reacting a compound containing at least two isocyanate groups in one molecule (hereinafter referred to as "isocyanate group-containing compound") with a compound containing at least two active hydrogen groups in one molecule (hereinafter referred to as "active hydrogen group-containing compound") as long as it does not have a silanol group in the molecule. The polyurethane resin A may be a known product or a commercially available product, or a polyurethane resin obtained by a known production method.

[0080] The isocyanate group-containing compound may be any of aliphatic diisocyanate, alicyclic diisocyanate, aromatic diisocyanate, aromatic aliphatic diisocyanate, etc. These may be used alone or in combination of two or more.

[0081] Examples of the aliphatic diisocyanate include trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,2-propylene diisocyanate, 1,2-butylene diisocyanate, 2,3-butylene diisocyanate, 1,3-butylene diisocyanate, 2,4,4- or 2,2,4-trimethylhexamethylene diisocyanate, 2,6-diisocyanate methyl hexanoate, or a mixture thereof; examples of the alicyclic diisocyanate include 1,3-cyclopentane diisocyanate, 1,4-cyclohexane diisocyanate, 1,3-cyclohexane diisocyanate, 3-isocyanate methyl-3,5,5-trimethylcyclohexyl isocyanate (isophorone diisocyanate), 4,4'-methylenebis(cyclohexyl isocyanate), methyl-2,4-cyclohexane diisocyanate, methyl-2,6-cyclohexane diisocyanate, 1,4-bis(isocyanate methyl)cyclohexane or 1,3-bis(isocyanate methyl)cyclohexane or a mixture thereof (hydrogenated xylylene diisocyanate), or a mixture thereof; as aromatic diisocyanates, for example Examples include: m-phenylene diisocyanate, p-phenylene diisocyanate, 4,4'-diphenyl diisocyanate, 1,5-naphthalene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4- or 2,6-toluene diisocyanate or a mixture thereof, 4,4'-toluidine diisocyanate, dianisidine diisocyanate, 4,4'-diphenyl ether diisocyanate, or a mixture thereof; examples of aromatic aliphatic diisocyanates include: 1,3- or 1,4-xylylene diisocyanate or a mixture thereof, ω, ω'-diisocyanate-1, 4-diethylbenzene, 1,3- or 1,4-bis(1-isocyanate-1-methylethyl)benzene or a mixture thereof; as triisocyanates, for example, triphenylmethane-4,4',4"-triisocyanate, 1,3,5-triisocyanatebenzene, 2,4,6-triisocyanatetoluene, 1,3,5-triisocyanatehexane, etc.; as polyisocyanate monomers, for example, 4,4'-diphenyldimethylmethane-2,2'-5,5'-tetraisocyanate, etc.; dimers and trimers derived from the above polyisocyanate monomers.

[0082] Examples of the active hydrogen group-containing compound include compounds having an amino group, a hydroxyl group, a mercapto group, etc., but compounds having a hydroxyl group (particularly a polyol) are preferred from the viewpoints of the reaction rate with an isocyanate group and the mechanical properties of the resulting coating.

[0083] Examples of the compound having a hydroxyl group include polyester polyol, polyolefin polyol, polyether polyol, polyether ester polyol, polyester amide polyol, acrylic polyol, polycarbonate polyol, polyhydroxyalkane, castor oil, polyurethane polyol, and mixtures thereof.

[0084] Examples of the polyester polyol include polyester polyols obtained by reacting dibasic acids such as terephthalic acid, isophthalic acid, adipic acid, azelaic acid, and sebacic acid, or dialkyl esters thereof, or mixtures thereof, with glycols such as ethylene glycol, propylene glycol, diethylene glycol, butanediol, neopentyl glycol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, 3,3'-dimethylolheptane, polyoxyethylene glycol, polyoxypropylene glycol, and polytetramethylene ether glycol, or mixtures thereof.

[0085] Examples of the polyolefin polyol include polyethylene polyol, polypropylene polyol, polyisobutylene polyol, hydrogenated polyisoprene polyol, and hydrogenated polybutadiene polyol.

[0086] Examples of the polyether polyol include polyether polyols obtained by polymerizing oxirane compounds such as ethylene oxide, propylene oxide, butylene oxide, and tetrahydrofuran using low molecular weight polyols such as water, ethylene glycol, propylene glycol, trimethylolpropane, and glycerin as initiators.

[0087] Examples of the polyetherester polyol include polyetherester polyols obtained by reacting the dibasic acid or dialkyl esters thereof or a mixture thereof with the polyetherpolyol. Examples of the polyesteramide polyol include polyesteramide polyols obtained by adding an amino group-containing aliphatic diamine such as ethylenediamine, propylenediamine, hexamethylenediamine, etc. as a raw material to the raw materials of the polyesterification reactant during the polyesterification reaction and reacting the aliphatic diamine as a raw material.

[0088] Examples of the acrylic polyol include acrylic polyols obtained by copolymerizing a polymerizable monomer having one or more hydroxyl groups in one molecule (e.g., hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, etc.) with, for example, (meth)acrylic acid or an ester thereof. One or more of these may be used.

[0089] Examples of the polycarbonate polyol include polycarbonate polyols obtained by reacting at least one of ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, 1,9-nonanediol, 1,8-nonanediol, neopentyl glycol, diethylene glycol, dipropylene glycol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, bisphenol A and hydrogenated bisphenol A with dimethyl carbonate, diphenyl carbonate, ethylene carbonate, phosgene, etc. These may be used alone or in combination.

[0090] Examples of the polyhydroxyalkane include liquid rubber obtained by copolymerizing isoprene, butadiene, or butadiene and acrylamide.

[0091] Examples of the polyurethane polyol include polyols having an urethane bond in one molecule, and examples of the polyol include polyols obtained by reacting polyether polyols, polyester polyols, polyether ester polyols, etc. with an isocyanate group-containing compound having at least 2 isocyanate groups per molecule as described later, when the molar number of (NCO group / OH group) is less than 1.

[0092] In addition to the above compounds having hydroxyl groups, diols such as ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,9-nonanediol, 1,8-nonanediol, neopentyl glycol, diethylene glycol, dipropylene glycol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, low molecular weight polyols such as glycerol, trimethylolpropane, neopentyletrol, methanol, ethanol, propanols, butanols, 2-ethylhexanol, lauryl alcohol, stearyl alcohol, etc. may be mixed. One or more of these may be used.

[0093] In addition, an anionic functional group (hydrophilic group) is preferably introduced into the polyurethane resin A. Examples of the anionic functional group include a carboxyl group, a sulfonic acid group, and a phosphoric acid group. Examples of methods for introducing anionic functional groups into the polyurethane resin include a method of using a diol having an anionic functional group as a polyol component, a method of using a diol having an anionic functional group as a chain extender, and the like. Examples of the diol having an anionic functional group include aliphatic carboxylic acids such as glyceric acid, dihydroxymaleic acid, dihydroxyfumaric acid, tartaric acid, dimethylolpropionic acid, dimethylolbutanoic acid, 2,2-dimethylol valeric acid, 2,2-dimethylolpentanoic acid, 4,4-di(hydroxyphenyl)valeric acid, and 4,4-di(hydroxyphenyl)butyric acid, and aromatic carboxylic acids such as 2,6-dihydroxybenzoic acid. One or more of these may be used.

[0094] The content of the polyurethane resin A in the primer layer is not limited, but is generally about 15 to 75% by mass, particularly preferably 15 to 70% by mass, and more preferably 20 to 60% by mass.

[0095] Polyurethane resin B

[0096] The polyurethane resin B only needs to contain at least one silanol group in the molecule. As the polyurethane resin B, a known product or a commercially available product may be used, or a polyurethane resin obtained by a known production method may be used.

[0097] The location where the silanol group contained in the polyurethane resin B exists (is bonded) is not particularly limited, and the silanol group may exist (be bonded) at both ends, either end, or any location in the middle of the polyurethane resin.

[0098] In addition, in the polyurethane resin B, an anionic functional group (hydrophilic group) is preferably introduced. As anionic functional groups, for example, carboxyl groups, sulfonic acid groups, phosphoric acid groups, etc. can be listed. As methods for introducing anionic functional groups into polyurethane resins, there can be listed: a method of using alcohols having anionic functional groups as polyol components, a method of using diols having anionic functional groups as chain extenders, etc. As diols having anionic functional groups, for example, there can be listed: glyceric acid, dihydroxymaleic acid, dihydroxyfumaric acid, tartaric acid, dimethylolpropionic acid, dimethylolbutyric acid, 2,2-dimethylol valeric acid, 2,2-dimethylol valeric acid, 4,4-di(hydroxyphenyl) valeric acid, 4,4-di(hydroxyphenyl) butyric acid and other aliphatic carboxylic acids, aromatic carboxylic acids such as 2,6-dihydroxybenzoic acid, etc. These can be used one or more.

[0099] The polyurethane resin B may be, for example, a polyurethane resin obtained by introducing a silanol group into the molecule by reacting a compound containing at least one active hydrogen group in one molecule and at least one hydrolyzable silicon group in one molecule (hereinafter referred to as a "hydrolyzable silicon group-containing compound") with a polyurethane compound obtained by reacting an isocyanate group-containing compound with an active hydrogen group-containing compound.

[0100] As a method for introducing a silanol group, similar to the case of anionic functional groups, examples include a method of using a diol having a silanol group as a polyol component, a method of using a diol having a silanol group as a chain extender, etc. Examples of the diol having a silanol group include at least one of silanediol, 1,3-disiloxane-1,3-diol, and diphenylsilanediol.

[0101] As the isocyanate group-containing compound, the active hydrogen group-containing compound, and the like, the same compounds as those described above with respect to the polyurethane resin A can be used.

[0102] The above-described compound containing a hydrolyzable silyl group may be any compound that contains at least one active hydrogen group in one molecule and at least one hydrolyzable silyl group in one molecule. Examples of the hydrolyzable silyl group include groups in which a hydrolyzable group generated upon hydrolysis in the presence or absence of a silanol condensation catalyst is bonded to a silicon atom. Examples of the hydrolyzable group include at least one of a hydrogen atom, a halogen atom, an alkoxy group, an acyloxy group, a ketoximate group, an amino group, an amide group, an aminooxy group, a mercapto group, and an alkenoxy group. Usually, 1 to 3 hydrolyzable groups are bonded to one silicon atom.

[0103] As specific examples of the compound containing a hydrolyzable silyl group, as a compound having a mercapto group as the active hydrogen group and an alkoxy group as the hydrolyzable group, for example, at least one of γ-mercaptopropyltrimethoxysilane, γ-mercaptopropylmethyldimethoxysilane, γ-mercaptopropyltriethoxysilane, γ-mercaptopropylmethyldiethoxysilane, etc. can be cited. In addition, as a compound having an amino group as the active hydrogen group and an alkoxy group as the hydrolyzable group, for example, at least one of γ-(2-aminoethyl)aminopropyltrimethoxysilane, γ-(2-aminoethyl)aminopropyltriethoxysilane, γ-(2-aminoethyl)aminopropylmethyldimethoxysilane, γ-(2-aminoethyl)aminopropylmethyldiethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldiethoxysilane, γ-aminopropyltrimethoxysilane, etc. can be cited.

[0104] The content of the polyurethane resin B in the undercoat is not particularly limited, but is usually set to about 15 to 75% by mass, particularly preferably set to 15 to 70% by mass, and further more preferably set to 20 to 60% by mass.

[0105] In addition, regarding the ratio of the polyurethane resin A to the polyurethane resin B, although not limited, when the total of the two is set to 100 parts by mass, the polyurethane resin A can be set to 25 to 80 parts by mass (preferably 30 to 80 parts by mass, more preferably 40 to 80 parts by mass, particularly preferably 55 to 80 parts by mass, and most preferably 65 to 80 parts by mass), and the polyurethane resin B can be set to 20 to 75 parts by mass (preferably 20 to 70 parts by mass, more preferably 20 to 60 parts by mass, particularly preferably 20 to 45 parts by mass, and most preferably 20 to 35 parts by mass). If the polyurethane resin A in the undercoat is more than 80 parts by mass, there will be a problem that the anti-blocking property decreases when the polyamide film is easily bonded in a rolled state. In addition, if the polyurethane resin B is more than 75 parts by mass, it will exceed the optimal amount of the silanol crosslinked structure, and unevenness will occur locally on the surface, so the printing appearance may be reduced. In addition, sometimes the adhesion to processing materials such as printing and adhesives applied to the undercoat may also decrease.

[0106] In the present invention, polyurethane resin A and polyurethane resin B use polyurethane resins with different glass transition temperatures (Tg). As a result, good blocking resistance, softness, etc. can be obtained in the temperature range between each glass transition temperature (Tg). The glass transition temperature (Tg) of polyurethane resin A is generally preferably about 5 to 50°C. Among them, the lower limit of Tg of polyurethane resin A is generally preferably above 5°C, particularly more preferably above 10°C, further more preferably above 15°C, and most preferably above 20°C. When Tg is less than 5°C, the blocking resistance of the rolled film may be reduced. In addition, when Tg is greater than 50°C, the softness of the primer layer will decrease, the stretch followability will deteriorate, and there will be a risk of damaging the appearance of the polyamide film.

[0107] The glass transition temperature (Tg) of the polyurethane resin B is usually preferably 60° C. or higher, more preferably 70° C. or higher, further preferably 85° C. or higher, and most preferably 100° C. or higher. When the Tg is less than 60° C., the heat resistance of the primer layer as a whole may be reduced, and the blocking resistance may be reduced. The upper limit of the Tg of the polyurethane resin B may be set to about 120° C., for example, but is not limited thereto.

[0108] The polyurethane resin A and / or B used in the present invention preferably has a film elongation of 200% or more. When the elongation of the polyurethane resin A or B is less than 200%, although the cohesive force of the resin film is improved, the flexibility and impact resistance of the film are sometimes reduced, and therefore, the adhesion with the processed object may be reduced, wherein the processed object is a processed object after the primer layer is coated, printed, or the like.

[0109] The tensile strength of the polyurethane resin A and / or B used in the present invention is preferably above 20MPa, particularly preferably above 25MPa, and more preferably above 30MPa. When the tensile strength of the polyurethane resin A and B is less than 20MPa, although the adhesion with the processed object will be improved, the heat resistance of the primer layer may be reduced. The processed object is: the primer layer is processed such as coating, printing, etc., and the processed object before hot water treatment. Therefore, after the primer layer is processed such as coating, printing, etc., the adhesion with the processed object after hot water treatment is easily greatly damaged. In addition, the cohesion of the resin film may be reduced, and the adhesion resistance is also reduced.

[0110] In view of the above, in the present invention, the film elongation of polyurethane resin A is preferably 300% or more, and the tensile strength is preferably 20 to 50 MPa. In addition, the film elongation of polyurethane resin B is preferably 200% or more, and the tensile strength is preferably 40 to 60 MPa.

[0111] In the film of the present invention, other additives may be contained in the primer layer within the range not hindering the effect of the present invention. However, since the curing agent (crosslinking agent) is preferably contained in a small amount or not for the above reasons, the content in the primer layer is set to 0.1% by mass or less.

[0112] In particular, in order to impart high blocking resistance through the primer layer, a lubricant may also be blended. For example, when the lubricant is in a particle form, a lubricant having an average particle size of 5 to 300 nm (particularly 10 to 200 nm) may be used. In addition, although its content is not limited, it is usually sufficient to be set to a range of 0 to 10% by mass in the primer layer. Therefore, for example, it may be set to 0.1 to 10% by mass, and from the viewpoint of improving blocking resistance and transparency, for example, it may be set to 0.1 to 5% by mass, preferably 0.3 to 3% by mass, and more preferably 0.5 to 2% by mass.

[0113] As the lubricant, at least one of an organic lubricant and an inorganic lubricant may be used. As the inorganic lubricant, for example, at least one of clay, talc, calcium carbonate, magnesium carbonate, zinc carbonate, wollastonite, silicon dioxide, aluminum oxide, calcium oxide, magnesium oxide, calcium silicate, sodium aluminate, calcium aluminate, magnesium aluminum silicate, hollow glass spheres, carbon black, zinc oxide, antimony trioxide, zeolite, hydrotalcite, layered silicate, sodium silicate, aluminum hydroxide, iron oxide, zirconium oxide, barium sulfate, titanium oxide, carbon black, etc. may be used. As the organic lubricant, for example, at least one of acrylic crosslinked polymers, styrene crosslinked polymers, phenolic resins, nylon resins, polyethylene wax, ethylene bis stearamide, etc. may be used.

[0114] In the film of the present invention, the total amount of volatile alkali components generated by the primer layer is preferably less than 0.50 ppm, and more preferably less than 0.20 ppm. If the volatile alkali components remain in the primer layer at more than 0.50 ppm, the water resistance of the primer layer may be reduced, and the adhesion between the primer layer and the processed material may be reduced, wherein the processed material is a processed material with water when the primer layer is processed by coating, printing, etc. In addition, it is easy to hinder the safety improvement effect when the easy-adhesion polyamide film is used in packaging materials for food, etc.

[0115] The thickness of the primer layer (thickness after stretching) is not limited, but it can usually be set to about 0.025 to 0.250 μm, and is particularly preferably set to 0.050 to 0.120 μm. If the thickness is less than 0.025 μm, it will be difficult to uniformly form a flawless coating on the film. As a result, after the primer layer is coated, printed, and processed, the adhesion between the processed material and the processed material may be reduced, and the processed material is a processed material after hot water treatment such as boiling and steaming. On the other hand, if the thickness is greater than 0.250 μm, there is a risk of deterioration of water resistance. In addition, since the terminal groups become easy to ooze out of the surface layer, there is a risk of reduced adhesion and an increase in the residual amount of volatile alkali components in the primer layer. In addition, since the improvement in adhesion is slight when it is thicker, it is also economically inefficient.

[0116] The thickness of the film of the present invention is not particularly limited, but is usually about 3 to 50 μm, and particularly preferably 10 to 25 μm. The film of the present invention is preferably a stretched film, and particularly more preferably a biaxially stretched film (a biaxially oriented crystallized film).

[0117] The film of the present invention has excellent blocking resistance. Therefore, the primer layers are superimposed on each other, a load of 10 kg / cm is applied, and the adhesion after 1 week at 40°C is preferably less than 40 g / 15 mm, more preferably less than 30 g / 15 mm, further more preferably less than 20 g / 15 mm, particularly preferably less than 15 g / 15 mm, and most preferably less than 10 g / 15 mm. In addition, the primer layer and the surface opposite to the primer layer are superimposed, a load of 10 kg / cm is applied, and the adhesion after 1 week at 40°C is preferably less than 10 g / 15 mm, more preferably less than 5 g / 15 mm, and particularly preferably less than 3 g / 15 mm. Although the lower limit of blocking resistance is not particularly limited, in any of the above cases, it is usually about 1 g / 15 mm.

[0118] In addition, the film of the present invention has excellent printability. Therefore, at any 10 locations in the TD direction of the printed film, the 2.5 mm diameter of the 50% gradation portion of the halftone printing printed on the primer layer was 2 After measuring the length of the area of ​​300 dots within the printing area, the minimum to maximum area ratio (average value of the 20 dots with the smallest area / average value of the 20 dots with the largest area) is preferably in the range of 0.8 to 1, more preferably in the range of 0.85 to 1, and most preferably in the range of 0.9 to 1. Within such a range, printing unevenness is small and a uniform printing state can be obtained.

[0119] The film of the present invention has good transparency and therefore good printing visibility. At this time, the haze value of the film of the present invention is usually preferably below 8%, particularly more preferably below 7%, and most preferably below 6%. Although the lower limit of the haze is not particularly limited, it is usually about 1%. As mentioned above, the film of the present invention has excellent blocking resistance, so even when a lubricant is used, a relatively small amount can be used. Accordingly, excellent blocking resistance and high transparency can be achieved at the same time.

[0120] The easy-adhesive polyamide film of the present invention has excellent adhesion to processed objects, and the processed objects are: processed objects when various secondary processing such as coating and ink printing are performed on the surface of the primer layer of the easy-adhesive polyamide film, that is, coating agents, inks, etc.; and the easy-adhesive polyamide film of the present invention can also have excellent adhesion to the sealing film due to the stacking of adhesive layers, etc. Therefore, the easy-adhesive polyamide film of the present invention can be used in the form of a laminate, which is a laminate formed by applying a sealing film as a secondary processing, and has a high utilization value as a base film for packaging, general industrial use, etc. In addition, it still has excellent adhesion even after hot water treatment such as boiling and steaming, and has excellent printability, so it is particularly suitable for use in the field of food packaging.

[0121] 2. Method for producing easy-adhesive polyamide film

[0122] The method for producing the film of the present invention is not limited, but can be preferably carried out by the following first method or second method.

[0123] (A) Method 1

[0124] The first method is a method for producing an easily adhesive polyamide film, which comprises the following steps:

[0125] (1) a step of applying an aqueous coating agent containing a polyurethane resin A having no silanol group and a polyurethane resin B having a silanol group on at least one surface of an unstretched polyamide film (coating step); and

[0126] (2) A step of biaxially stretching the polyamide film coated with the aqueous coating agent and then performing a heat treatment (stretching step).

[0127] Coating process

[0128] In the coating step, an aqueous coating agent including a polyurethane resin A having no silanol group and a polyurethane resin B having a silanol group is coated on at least one surface of an unstretched polyamide film.

[0129] The above-mentioned unstretched polyamide film eventually becomes the polyamide substrate film of the film of the present invention. Therefore, its composition, etc. can adopt the composition described in the above-mentioned "1. Easy-to-adhere polyamide film". The unstretched polyamide film can be manufactured by forming a melt-kneaded product containing a polyamide resin into a sheet. The preparation of the melt-kneaded product itself can be implemented according to a known method. For example, the raw material containing the polyamide resin can be placed in an extruder equipped with a heating device, and heated to a specified temperature to melt it, and then the melt-kneaded product can be extruded through a T-die, and cooled and solidified by a drum casting machine, etc., thereby obtaining an unstretched sheet as a sheet-like formed body. The average thickness of the unstretched sheet at this time can be appropriately set according to the final thickness, etc., for example, it can be set to about 15 to 250 μm, and in addition, for example, it can be set to about 50 to 235 μm, but it is not limited to these.

[0130] The aqueous coating agent can be prepared by dispersing polyurethane resin A, polyurethane resin B, etc. in water. In particular, when polyurethane resin A and polyurethane resin B are anionic polyurethane resins, it is desirable to use a volatile base in order to disperse them in water. The volatile base is not particularly limited, and examples thereof include at least one of ammonia, methylamine, ethylamine, dimethylamine, diethylamine, triethylamine, thiophene, ethanolamine, etc. Among them, triethylamine is more preferred because the liquid stability of the water-dispersible polyurethane resin is good and the boiling point is relatively low, so the residual amount in the primer layer is small.

[0131] When the coating agent is applied to the substrate film, in order to further improve the coating property, a surfactant can also be added to the aqueous coating agent. The surfactant can promote the wetting of the aqueous coating agent to the substrate film. For example, anionic surfactants such as polyethylene alkylphenyl ether, polyoxyethylene-fatty acid ester, glycerol fatty acid ester, fatty acid metal soap, alkyl sulfate, alkyl sulfonate, alkyl sulfosuccinate, and non-ionic surfactants such as acetylene glycol can be listed. These can be used in one or more than two kinds. Although the content of the surfactant is not limited, it is preferably contained in the aqueous coating agent in an amount of 0.01 to 1% by mass. If it is greater than 1% by mass, there will be a risk of reducing the adhesion after hot water treatment such as boiling and steaming treatment due to the surfactant seeping out or remaining in the primer. Therefore, the surfactant used is preferably a surfactant that volatilizes during the heat treatment of the manufacturing process of the easy-to-bond polyamide film.

[0132] As the aqueous coating agent, a known or commercially available water-dispersible polyurethane resin (particularly anionic water-dispersible polyurethane resin) can be used. Examples of the water-dispersible polyurethane resin A include: product names “Hydran ADS-110”, “Hydran ADS-120”, “Hydran KU-400SF”, “Hydran HW-311”, “Hydran HW-312B”, “Hydran HW-333”, “Hydran AP-20”, “Hydran AP-201”, “Hydran AP-80”, “Hydran APX-101H”, and “Hydran AP-60LM” (all manufactured by DIC Corporation); product names “Superflex 107M”, “Superflex 150”, “Superflex 150HS”, “Superflex 410”, “Superflex 420NS”, “Superflex 460”, “Superflex 460S”, “Superflex 700”, “Superflex 750”, and “Superflex 840” (all manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd.); product names “Takerack W-6010”, “Takerack The water-dispersible polyurethane resin B includes, for example, product names “Takerack WS-4000”, “Takerack WS-4022”, “Takerack WS-5000”, “Takerack WS-5100”, and “Takerack WS-6010” (all manufactured by Mitsui Chemicals, Inc.).

[0133] The solid content concentration of the polyurethane resin in the water-based coating agent is not limited, and can be appropriately changed, for example, by the specifications of the coating device and the drying / heating device. At this time, for a solution that is too thin, it may take a long time in the drying process. On the other hand, if the solid content concentration is too high, it is difficult to obtain a uniform coating agent, and it may also hinder the coating property. From such a point of view, the solid content concentration in the water-based coating agent is usually preferably set to a range of about 3 to 35% by mass.

[0134] The method for applying the aqueous coating agent to the polyamide film is not particularly limited, and examples thereof include common methods such as gravure roll coating, reverse roll coating, wire bar coating, and air knife coating.

[0135] After the aqueous coating agent is applied, a drying step may be performed as necessary. The drying method may be either natural drying or heat drying, and for example, a method of drying by heating at 100 to 180° C. is preferably used.

[0136] Stretching process

[0137] In the stretching process, the polyamide film coated with the aqueous coating agent is biaxially stretched and then heat-treated. More specifically, in the first method, the aqueous coating agent whose main component is an anionic water-dispersible polyurethane resin is applied to at least one side of an unstretched polyamide substrate film to form a coating film, and then the unstretched polyamide film is biaxially stretched together with the coating film, and then heat-treated, thereby biaxially oriented the crystals of the polyamide film.

[0138] In the first method, a simultaneous biaxial stretching method can be appropriately used as the stretching method. The stretching temperature is usually set to about 70 to 250° C., and is particularly preferably set to 100 to 230° C. The stretching ratio can be appropriately set according to, for example, the application, the desired physical properties, etc., for example, it can be set to about 2 to 4 times in the MD direction and about 2 to 4 times in the TD direction, but is not limited thereto.

[0139] Heat treatment after stretching For example, a film stretched with both ends in the width direction held can be appropriately heat treated (ie, heat-set) directly with both ends in the width direction held.

[0140] In the manufacturing method of the present invention, the temperature of heat setting is usually preferably 180 to 250°C, and particularly preferably 210 to 230°C. If the temperature of heat setting is less than 180°C, the thermal dimensional stability of the stretched oriented film will become higher, and the amount of volatile alkali components remaining in the primer layer will increase. Therefore, the adhesion to the processed object, which is the object of the present invention, is easily reduced, and the processed object is: the processed object when it is wet after the primer layer is coated, printed, etc. In addition, if the temperature of heat setting is greater than 250°C, it will become a temperature above the melting point of the polyamide resin, and there may be a situation where the desired stretched film cannot be obtained.

[0141] (B) Method 2

[0142] The second method is a method for producing an easily adhesive polyamide film, which comprises the following steps:

[0143] (1) a step of uniaxially stretching an unstretched polyamide film in a first direction (a first stretching step);

[0144] (2) a step of coating at least one surface of the uniaxially stretched polyamide film with an aqueous coating agent containing a polyurethane resin A having no silanol group and a polyurethane resin B having a silanol group (coating step); and

[0145] (3) A step of uniaxially stretching the polyamide film coated with the aqueous coating agent in a second direction perpendicular to the first direction and then heat treating the film (second stretching step).

[0146] 1st stretching process

[0147] In the first stretching step, the unstretched polyamide film is uniaxially stretched in the first direction. More specifically, the unstretched polyamide film is stretched in the first direction by a roller group with different peripheral speeds heated to 45 to 80° C. (preferably 50 to 60° C.). The stretching ratio at this time can be appropriately set according to, for example, the application, the desired physical properties, etc., for example, it can be set to 2 to 4 times in the MD direction or TD direction, but is not limited thereto. The above-mentioned unstretched polyamide film eventually becomes the polyamide substrate film of the film of the present invention. Therefore, its composition, etc. can adopt the composition described above, etc. The unstretched polyamide film can be made in the same way as the first method.

[0148] Coating process

[0149] In the coating step, an aqueous coating agent containing a polyurethane resin A having no silanol group and a polyurethane resin B having a silanol group is coated on at least one surface of the uniaxially stretched polyamide film. The aqueous coating agent, coating conditions, etc. may be set in the same manner as in the first method.

[0150] Second stretching process

[0151] In the second stretching step, the polyamide base film coated with the aqueous coating agent is uniaxially stretched in a second direction perpendicular to the first direction, and then heat-treated.

[0152] The film is held at both ends in the width direction and stretched in the second direction at a temperature of 70 to 150° C. (preferably 80 to 120° C.). The stretching ratio at this time can be appropriately set according to, for example, the application, the desired physical properties, etc., and can be set to, for example, about 2 to 4 times in the TD direction or the MD direction, but is not limited thereto.

[0153] The reason why the stretching temperature of the sequential biaxial stretching method adopted in the second method is lower than the stretching temperature of the simultaneous biaxial stretching method in the first method is that if the sequential biaxial stretching method is used for high-temperature stretching, the degree of crystallinity of the polyamide film will become too high, and it will become impossible to stretch at the required ratio, or the required physical properties of the polyamide film will be greatly damaged.

[0154] Thus, the film of the present invention obtained by the first method or the second method may be subjected to surface treatments such as corona discharge treatment and easy bonding treatment within the scope of not damaging the effect of the present invention. In addition, an easy bonding layer, a barrier coating, a printing layer, etc. may be appropriately provided as required. In particular, by applying a corona discharge treatment to the surface opposite to the primer, in addition to being suitable for surface printing, it may also be suitable for use as an intermediate layer of a multi-layer laminated laminate, etc.

[0155] 3. Application of easy-to-bond polyamide film

[0156] The film of the present invention (especially the biaxially stretched film) obtained by operating as described above has excellent mechanical properties such as tensile elongation, tensile strength, elastic modulus, etc. as a polyamide resin film, and also has excellent transparency, color tone, wettability, printability, etc., and can therefore be particularly suitably used as a packaging material.

[0157] The film of the present invention can be used alone or in the form of a laminate by laminating with other layers.

[0158] As other layers, there is no limitation, and barrier layers, printed layers, laminated adhesive layers, heat seal layers, resin films, etc. may be appropriately provided as required. In particular, the present invention also includes a laminate (the present invention laminate) in which at least a laminated adhesive layer and a heat seal layer are sequentially laminated directly or via a printed layer on the primer layer of the present invention film. For example, Figure 2 As shown in the figure, a primer layer 12 is formed on one side of a polyamide substrate film 11, a printed layer 13 is laminated on the primer layer, and a laminated adhesive layer 14 and a heat seal layer 15 are further formed on the printed layer. As the laminated adhesive layer or the heat seal layer, for example, a resin layer containing polyolefins such as polyethylene and polypropylene can be used. These can also use well-known products or commercial products. In the present invention, the case where other layers are further included on such a laminate is also included in the laminate of the present invention.

[0159] For example, a corona discharge treatment may be applied to the surface of the film of the present invention opposite to the primer layer, and a laminated body may be prepared in which a laminated adhesive layer and a resin film are laminated in this order directly or via a printed layer. Specifically, the following may be mentioned:

[0160] (a) polyester resin film / laminated adhesive layer / polyamide substrate film / primer layer / laminated adhesive layer / heat seal layer;

[0161] (b) polyester resin film / printing layer / laminated adhesive layer / polyamide substrate film / primer layer / laminated adhesive layer / heat sealing layer;

[0162] (c) polyester resin film / laminated adhesive layer / polyamide substrate film / primer layer / printing layer / laminated adhesive layer / heat sealing layer;

[0163] (d) polyamide resin film / laminated adhesive layer / polyamide substrate film / primer layer / laminated adhesive layer / heat seal layer;

[0164] (e) polyamide resin film / printing layer / laminated adhesive layer / polyamide substrate film / primer layer / laminated adhesive layer / heat sealing layer;

[0165] (f) polypropylene resin film / laminated adhesive layer / polyamide substrate film / primer layer / laminated adhesive layer / heat sealing layer;

[0166] (g) polypropylene resin film / printing layer / laminated adhesive layer / polyamide substrate film / primer layer / laminated adhesive layer / heat sealing layer;

[0167] (h) Polypropylene resin film / laminated adhesive layer / polyamide base film / primer layer / printing layer / laminated adhesive layer / heat seal layer

[0168] It should be noted that the "polyamide substrate film / primer layer" in these examples corresponds to the film of the present invention. Specific examples of each layer are shown below.

[0169] The barrier layer is a layer for blocking air, moisture, etc. Examples of the barrier layer include aluminum foil, vapor deposited layers of aluminum and silicon oxide, polyvinylidene chloride (PVDC) coatings, polycarboxylates, and hydrogen-bonding resin-inorganic layered compound composite layers.

[0170] The printed layer is a layer printed with, for example, text, patterns, etc. There are no particular limitations on the ink used to form the printed layer. For example, toluene-containing ink, non-toluene ink, water-based ink, etc. may be cited. If environmental aspects are taken into consideration, at least one of non-toluene ink, water-based ink, etc. is preferred.

[0171] As the adhesive forming the laminated adhesive layer, a known product or a commercially available product can be used. For example, isocyanate-based, polyurethane-based, polyester-based, polyethyleneimine-based, polybutadiene-based, polyolefin-based, and alkyl titanate-based adhesives can be listed. Among them, from the viewpoints of adhesion, heat resistance, water resistance, etc., at least one adhesive selected from the group consisting of isocyanate-based, polyurethane-based, and polyester-based adhesives is preferred.

[0172] The heat seal layer is not particularly limited as long as it has heat sealability, and for example, at least one of low-density polyethylene, linear low-density polyethylene, high-density polyethylene, ethylene-vinyl acetate copolymer, polypropylene, and ionomer resin can be used.

[0173] The resin film is not limited, but examples thereof include at least one of a polyester resin film, a polyamide resin film, and a polypropylene resin film.

[0174] The laminate of the present invention can be produced by a method including laminating an adhesive layer or a heat seal layer on the primer layer or a printed layer formed thereon as required, using a known method such as dry lamination or extrusion lamination.

[0175] The laminate of the present invention can be used as a packaging bag (bag body) by heating and melting the facing laminated adhesive layers or heat-sealing layers. The bag body can be any of the following forms, for example: a double-side sealed bag, a three-side sealed bag, a back-sealed bag, a gusset bag, a side-sealed bag, a stand-up bag, a stand-up ziplock bag, etc.

[0176] The packaged article (content) is also not limited, and the package is widely used as a packaging material for food and beverages, as well as medicines, cosmetics, chemicals, sundries, and the like.

[0177] In the laminate of the present invention, whether or not there is a printed layer, the lamination strength (X) before hot water treatment in the normal state with water in the primer layer is preferably 3.0N / cm or more, more preferably 3.5N / cm or more, further more preferably 4.0N / cm or more, particularly preferably 4.5N / cm or more, and most preferably 5.0N / cm or more. In addition, the ratio (Y / X) of the lamination strength (Y) in water after hot water treatment at 120°C for 30 minutes to the lamination strength (X) in normal state with water is preferably 0.5 or more. The above ratio (Y / X) is preferably 0.6 or more, more preferably 0.7 or more, and particularly more preferably 0.8 or more, wherein the most preferably 0.9 or more. If the above ratio (Y / X) is less than 0.5, for example, a packaging bag is formed with a laminate, filled with contents and sealed, and then subjected to hot water treatment, it becomes easy to break the bag, open the seal, etc.

[0178] Example

[0179] The following examples and comparative examples are shown to more specifically illustrate the features of the present invention. However, the scope of the present invention is not limited by the examples. It should be noted that the urethane latex (water-dispersible polyurethane resin) used in the examples and comparative examples is an anionic polyurethane aqueous dispersion.

[0180] 1. Polyurethane resins used in Examples and Comparative Examples

[0181] <Polyurethane resin A having no silanol group>

[0182] ・AP-201: DIC Corporation's water-dispersible polyurethane resin "Hydran AP-201"

[0183] ・AP-80: DIC Corporation's water-dispersible polyurethane resin "Hydran AP-80"

[0184] ・Polyurethane resin A-1: ​​Polyurethane resin obtained by the following method

[0185] In a reaction container equipped with a thermometer, a nitrogen inlet pipe and a stirrer, 166.1 parts by mass of terephthalic acid, 36.5 parts by mass of adipic acid, 46.6 parts by mass of ethylene glycol, 67.6 parts by mass of 1,4-butanediol and 0.1 parts by mass of dibutyltin oxide were charged while introducing nitrogen, and a polycondensation reaction was carried out at 230° C. for 6 hours until the acid value became 1 or less, thereby obtaining a polyester polyol having a number average molecular weight of 1500, an acid value of 0.1 and a hydroxyl value of 72.9.

[0186] 300 parts by mass of the obtained polyester polyol was dehydrated by heating at 100° C. under reduced pressure. Next, 144.2 parts by mass of methyl ethyl ketone was supplied to the above reaction container adjusted to 80° C., 26.8 parts by mass of 2,2-dimethylol propionic acid and 18.0 parts by mass of 1,4-butanediol were supplied, and 104.5 parts by mass of toluene diisocyanate were supplied, and the mixture was reacted at 75° C. for 8 hours. Next, 20.2 parts by mass of triethylamine was supplied to the above reaction container adjusted to 50° C. for neutralization, and 300 parts by mass of water was supplied and mixed. Methyl ethyl ketone was removed from the mixture obtained above under reduced pressure, and water was supplied, thereby obtaining a polyurethane resin A-1 having a solid content concentration of 25% by mass.

[0187] ・Polyurethane resin A-2: Polyurethane resin obtained by the following method

[0188] Polyurethane resin A-2 was obtained in the same manner as in the above-mentioned polyurethane resin A-1 except that terephthalic acid was used in 166.1 parts by mass and adipic acid was used in 219.2 parts by mass.

[0189] ・Polyurethane resin A-3: Polyurethane resin obtained by the following method

[0190] In a reaction container equipped with a thermometer, a nitrogen inlet pipe and a stirrer, 120.97 parts by mass of methyl ethyl ketone was supplied while introducing nitrogen and the temperature was adjusted to 70°C. 26.8 parts by mass of 2,2-dimethylolpropionic acid and 106.4 parts by mass of 1,6-hexanediol, 13.4 parts by mass of trimethylolpropane and 319.9 parts by mass of meta-xylylene diisocyanate were supplied and reacted at 70°C until it was confirmed that the reaction liquid reached the specified amine equivalent. Next, 20.2 parts by mass of triethylamine was added to the above reaction container adjusted to 35°C. Next, 1440 parts by mass of water was added to a reaction container equipped with a homogenizer capable of high-speed stirring, the temperature was adjusted to 15°C, and the mixture was stirred at 2000 min. -1The mixture was stirred and mixed, and the obtained mixture was added to disperse in water, and an aqueous amine solution containing 41.7 parts by mass of 2-[(2-aminoethyl)amino]ethanol and 180 parts by mass of water was added to carry out a chain extension reaction. Thereafter, methyl ethyl ketone and part of the water were removed under reduced pressure, thereby obtaining a polyurethane resin A-3 having a solid content concentration of 25% by mass.

[0191] <Polyurethane resin B having silanol group>

[0192] ・WS-4022: Mitsui Chemicals "Takerack WS-4022"

[0193] ・WS-5000: Mitsui Chemicals "Takerack WS-5000"

[0194] ・Polyurethane resin B-1: Polyurethane resin obtained by the following method

[0195] Polyurethane resin B-1 was obtained in the same manner as in polyurethane resin A-3 except that an amine aqueous solution obtained by mixing 4.4 parts by mass of N-2-(aminoethyl)-3-aminopropyltrimethoxysilane and 18 parts by mass of water was added during the chain extension reaction.

[0196] 2. Examples and Comparative Examples

[0197] Example 1

[0198] (1) Preparation of aqueous coating agent (aqueous dispersion)

[0199] A water-dispersible polyurethane resin "Hydran AP-201" manufactured by DIC Corporation and "Takerack WS-4022" manufactured by Mitsui Chemicals, Inc. were mixed in a ratio of 1:1 (solid content mass ratio), and silica particles with an average particle size of 12 nm were added to make 0.25% by mass of the whole, and diluted with ion-exchanged water to prepare an aqueous coating agent with a solid content of 10% by mass.

[0200] (2) Preparation of unstretched polyamide film

[0201] Nylon 6 (relative viscosity: 3.03) containing 0.1% by mass of silica with an average particle size of 1.0 μm was extruded from a T-die in a sheet form at 270° C. through an extruder equipped with a T-die (diameter 75 mm, slow compression type uniaxial screw with L / D=45), and rapidly cooled by making it close to a flow coating roll whose surface temperature was adjusted to 18° C., thereby obtaining an unstretched polyamide film with a thickness of 150 μm. The unstretched polyamide film was introduced into a water tank and adjusted to a water absorption rate of 4.0% by mass.

[0202] (3) Production of easy-adhesive polyamide film

[0203] After the above-mentioned aqueous coating agent is applied to the water-absorbed unstretched polyamide film by air knife coating, it is dried in a dryer at 60°C × 10 seconds. The coated unstretched film is introduced into a simultaneous biaxial stretching machine, and the preheating temperature is 225°C, the preheating time is 5 seconds, the stretching temperature is 195°C, and the stretching time is 3 seconds. The conditions are simultaneously biaxially stretched to 3.3 times in the longitudinal direction and 3.0 times in the transverse direction. Next, heat treatment is applied under the conditions of a heat setting temperature of 215°C and a heat setting time of 5 seconds, thereby making an easy-to-bond polyamide film. The thickness of the polyamide substrate film in the obtained easy-to-bond polyamide film is 15μm, and the thickness of the primer layer is 0.060μm.

[0204] [Examples 2 to 4]

[0205] Except having changed the mixing ratio of the aqueous polyurethane resin used for the aqueous coating agent as shown in Table 1, the same procedure as in Example 1 was carried out to prepare an easily adhesive polyamide film.

[0206] [Example 5]

[0207] An easily adhesive polyamide film was prepared in the same manner as in Example 1 except that the mixing ratio of the aqueous polyurethane resin used in the aqueous coating agent was changed as shown in Table 1, and the average particle size of the lubricant added to the aqueous coating agent was changed to 20 nm and the amount added was changed to 0.25 mass %.

[0208] [Example 6]

[0209] An easily adhesive polyamide film was produced in the same manner as in Example 1 except that a monomer obtained by depolymerizing resin scraps (resin waste materials) including film scraps or defective products generated during the production of polyamide 6 resin films and oligomers generated during the polymerization of polyamide 6 resin was used as a polymerization raw material.

[0210] [Examples 7 to 9]

[0211] An easily adhesive polyamide film was prepared in the same manner as in Example 1 except that the type of the aqueous polyurethane resin (A) used in the aqueous coating agent was changed to "Hydran AP-80" manufactured by DIC Corporation and the mixing ratio and the amount of lubricant added were changed as shown in Table 1.

[0212] [Example 10]

[0213] An easily adhesive polyamide film was prepared in the same manner as in Example 1 except that the type of the aqueous polyurethane resin (B) used in the aqueous coating agent was changed to "Takerack WS-5000" manufactured by Mitsui Chemicals, Inc. and the mixing ratio was changed as shown in Table 1.

[0214] [Examples 11 to 14]

[0215] Except having changed the kind of water-based polyurethane resin used for the water-based coating agent as shown in Table 1, it carried out similarly to Example 1, and produced the easy-adhesion polyamide film.

[0216] [Example 15]

[0217] After preparing an easily adhesive polyamide film in the same manner as in Example 1, an easily adhesive polyamide film was prepared by subjecting the surface opposite to the surface on which the primer layer was formed to a corona discharge treatment.

[0218] [Comparative Examples 1 to 11, 16, 18, 19]

[0219] An easily adhesive polyamide film was prepared in the same manner as in Example 1 except that the average particle diameter and the addition amount of the aqueous polyurethane resin and the lubricant used in the aqueous coating agent were changed as shown in Table 1.

[0220] [Comparative Example 12]

[0221] An easily adhesive polyamide film was prepared in the same manner as in Example 1 except that the aqueous polyurethane resin used in the aqueous coating agent was changed to only "Hydran AP-201" manufactured by DIC Corporation, and an easily adhesive polyamide film was prepared by applying corona discharge treatment on the surface opposite to the surface on which the primer layer was formed.

[0222] [Comparative Examples 13-14]

[0223] The aqueous polyurethane resin used for the aqueous coating agent was changed as shown in Table 1, and 4 parts by mass of a crosslinking agent carbodiimide (V-12-S manufactured by Nisshinbo Co., Ltd.) was added to 100 parts by mass of the polyurethane resin. In addition, the average particle size and addition amount of the lubricant were changed as shown in Table 1 in the same manner as in Example 1, and the easy-adhesion polyamide film was produced in the same manner as in Example 1.

[0224] [Comparative Example 15]

[0225] "Hydran KU-400SF" was used as a water-based polyurethane resin for a water-based coating agent, and 6 parts by mass of melamine (BECKAMINE APM manufactured by DIC Corporation) was added as a crosslinking agent to 100 parts by mass of the polyurethane resin. In addition, the average particle size and addition amount of the lubricant were changed as shown in Table 1 in the same manner as in Example 1, and an easy-adhesion polyamide film was prepared in the same manner as in Example 1.

[0226] [Comparative Example 17]

[0227] A polyamide film was produced in the same manner as in Example 1 except that the aqueous coating agent was not used, and a polyamide film was produced in which one surface was subjected to a corona discharge treatment.

[0228] [Test Example 1]

[0229] The properties of the films obtained in Examples 1 to 15 and Comparative Examples 1 to 19 were investigated. The results are shown in Tables 1 and 2 together with the composition and properties of the aqueous coating agent (polyurethane resin) etc. forming the primer layer.

[0230] (1) About polyurethane resin

[0231] (1-1) Tensile strength (MPa) and elongation (%)

[0232] Each polyurethane resin (dispersion liquid) (Table 1-Table 2) used as an aqueous coating agent for forming a primer layer was cast on a glass plate, dried at room temperature (about 20°C) for 24 hours, and then heat-treated at 150°C for 10 minutes to prepare a film with a thickness of 50 μm. The film was cut into a rectangular test piece with a width of 5 mm, and the tensile strength and elongation were measured using a tensile tester (AGS-100B manufactured by Shimadzu Corporation) at a tensile speed of 300 mm / min.

[0233] (1-2) Glass transition temperature Tg (℃)

[0234] Using a differential scanning calorimeter (Diamond DSC) manufactured by PerkinElmer Japan, 10 mg of the film used in (1-1) was heated once at 20°C / min to Tg+20°C, cooled, and then measured again at a heating rate of 5°C / min from -30°C to 250°C. The midpoint between the start temperature and the end temperature at which the baseline of the secondary heating curve shifted was taken as the glass transition temperature.

[0235] (2) About membrane

[0236] (2-1) Wetting tension (mN / m)

[0237] The primer-coat-formed surface of the easily adhesive polyamide film obtained in each of the Examples and Comparative Examples was measured using mixed solution No. 36.0 to 54.0 for wetting tension test (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) in accordance with Japanese Industrial Standard JIS K6768.

[0238] (2-2) Thickness of primer layer (μm)

[0239] The easy-adhesive polyamide films obtained in each embodiment and comparative example were cut into appropriate sizes using a JEM-1230 TEM manufactured by JEOL Ltd., immersed in a phosphotungstic acid aqueous solution (PTA solution) for 3 hours, and then embedded in a visible light curable resin. An 80 nm thick slice was taken with an ultrathin slicer, 1H vapor-stained with a RuO4 solution, and then transmission measurement was performed at an accelerating voltage of 100 kV.

[0240] (2-3) Haze

[0241] The center portion of the film in the TD direction was measured using a haze meter "NDH4000" manufactured by Nippon Denshoku Co., Ltd. in accordance with Japanese Industrial Standard JIS K7136.

[0242] (2-4) Anti-blocking

[0243] The easy-to-adhesive polyamide film obtained in each embodiment and comparative example was cut into A4 size, (a) the primer layers were overlapped with each other or (b) the primer layers were overlapped with the opposite side of the primer layers, a load of 10 kg / cm was applied, and the film was placed in an atmosphere of 40°C and 70% RH for 1 week. Among them, in Comparative Example 13, (a) the corona discharge treated surfaces were overlapped with each other or (b) the corona discharge treated surfaces were overlapped with the opposite side of the corona discharge treated surfaces. After that, the film was cut into strips with a width of 15 mm, and a tensile tester (AGS-100B manufactured by Shimadzu Corporation) was used to measure the peeling force (g / 15 mm) required to peel off two sheets under the condition of a tensile speed of 300 mm / min by the T-type (90°) method, which was used as an indicator of blocking resistance. The smaller the value, the better the blocking resistance.

[0244] (2-5) Halftone Printing Evaluation

[0245] [Printing process]

[0246] (a) Printing ink 1

[0247] The diluent NKFS102 (TOYOINK) was mixed into LIOALPHA R39 blue (TOYOINK) and the viscosity (23°C) was adjusted to 15 seconds in Zahn cup #3. The film roll for printing can be prepared by cutting the film at a position of 500 mm from the center in the TD direction. The ink was applied to the base coat layer of the film using a gravure printing cylinder, dried at 50°C for 10 seconds, and rolled up to prepare the following. Figure 3 In Comparative Example 14, the ink was applied on the corona discharge treated surface.

[0248] The above cylinder is Helio engraved with 175 lines (175 dots on a width of 1 inch) in the order of 40%, 50%, 60%, 70%, 80%, 90%, and 100% in the MD direction. The depth of each gradation is 10.0μm, 12.5μm, 15.0μm, 17.5μm, 20.0μm, 22.5μm, and 32.0μm, respectively. The printing length of each gradation in the MD direction is set to 60mm, and the printing width in the TD direction is set to 0.8m.

[0249] LIOALPHA R39 Blue mainly comprises 10% by mass of pigment, 15% by mass of synthetic resin, 2.5% by mass of silica, 30% by mass of ethyl acetate, 15% by mass of isopropyl alcohol, 10% by mass of propyl acetate, 10% by mass of propylene glycol monomethyl ether, and 5% by mass of n-propyl alcohol.

[0250] The diluent NKFS102 mainly contains 50% by mass of ethyl acetate, 35% by mass of propyl acetate, 10% by mass of isopropyl alcohol, and 5% by mass of n-propyl alcohol.

[0251] (b) Printing ink 2

[0252] A printed film was produced in the same manner as above except that BelleFlora R Blue 800MK (manufactured by Sakata Inx) which is an eco-friendly ink containing plant-derived components was used as printing ink 2 using diluent L Solvent 2 (manufactured by Sakata Inx).

[0253] BelleFlora R Blue 800MK has 45% by mass of n-propyl acetate, 15% by mass of isopropyl alcohol, 7.5% by mass of ethyl acetate, and 2.5% by mass of n-propyl alcohol as main components.

[0254] The L solvent 2 mainly contains 40% by mass of toluene, 40% by mass of methyl ethyl ketone, and 20% by mass of isopropyl alcohol.

[0255] [Dot area evaluation]

[0256] The position 250 mm from the end of the 50% gradation portion of the printed film produced with printing ink 1 was set as the first point, and a total of 10 points at intervals of 50 mm were set as measurement points (area 2.5 mm 2 The sample was taken in an observable size (e.g. 20 mm in the MD direction and 50 mm in the TD direction centered on the measurement point) and observed using a stereo microscope (Stereo Discovery.V12 manufactured by ZEISS). The 2.5 mm 2The diameter of the 300 dots within the screen is measured and the area is calculated. If the dots are elliptical, the length of the long side and the short side is measured and the area is calculated as an ellipse. Among all the dot areas, the average of the 20 with the smallest area and the average of the 20 with the largest area are calculated. The larger the value (the closer to 1), the less uneven printing.

[0257] [Printing appearance evaluation]

[0258] Each gradation portion of the produced printed film was visually observed and evaluated in 4 levels according to the following criteria. Practically, an evaluation of "△" to "◎" is desirable.

[0259] (Evaluation Criteria)

[0260] ◎…Very good (even shades in all gradations)

[0261] ○…Good (Printing unevenness was observed in a part of the low-tone portion.)

[0262] △… Slightly poor (Some unevenness was observed in all gradations.)

[0263] ×…Poor (Overall unevenness was observed in any gradation portion.)

[0264] (2-6) Lamination strength of printed film

[0265] [Lamination process]

[0266] The printed layer of the printed film produced using printing ink 1 or printing ink 2 in the above (2-5) is coated with a dry lamination adhesive for steaming purposes (manufactured by DIC Corporation. Product name "DICDRY LX500 / KR90S"), and then dried at 80°C × 10 seconds, and dry-laminated with an unstretched polypropylene film (manufactured by Mitsui Chemicals Tohcello Co., Ltd., product name "RXC-21", thickness 50 μm) on a metal roll heated to 80°C at a clamping pressure of 490 kPa, and aged for the recommended time to obtain a laminated film.

[0267] [Lamination strength measurement]

[0268] A test piece with a width of 15 mm was cut out from the produced laminated film, and the end of the test piece was peeled off at the interface between the unstretched polypropylene film and the primer layer of the easily adhesive polyamide film, and then the humidity was adjusted for 24 hours in an atmosphere of 23° C. and 50% RH. In this atmosphere, the peel strength was measured by a T-type (90°) method at a tensile speed of 300 mm / min using a tensile tester (“AGS-100B” manufactured by Shimadzu Corporation), and the measurement result was used as the laminate strength (unit: N / cm).

[0269] The produced laminated film was cut into A4 size, bagged, and placed in water for retorting (120° C., 1.8 atmospheres, 30 minutes). Thereafter, sampling was performed in the same manner as above, and the laminate strength was measured.

[0270] It should be noted that in this peel test, based on actual use, the test is performed while attaching absorbent cotton containing water to the peeling interface, assuming that the test piece is filled with liquid as a content, thereby measuring the water-containing laminate strength in a state where water is present on the peeling interface.

[0271] In addition, for each lamination strength, the ratio (Y / X) of the lamination strength after treatment (Y) to the lamination strength before treatment (X) was determined. The results are also shown in Table 2.

[0272] (2-7) Gas boiling test

[0273] [Lamination process]

[0274] The primer-coated surface of the easily-adhesive polyamide film obtained in each of the examples and comparative examples was coated with a dry lamination adhesive (manufactured by Mitsui Chemicals, product name "Takerack A-620 / Takenate A-65"), dried at 80°C x 10 seconds, and dry-laminated with an unstretched polypropylene film (manufactured by Mitsui Chemicals Tohcello, product name "TUX (HC-E)", thickness 50 μm) at a clamping pressure of 490 kPa on a metal roll heated to 80°C, and aged for the recommended time to obtain a laminated film.

[0275] [Gas boiling test]

[0276] The bag is made by sealing the laminated film in three directions with a size of 150mm×150mm (sealing width 10mm) and sealing conditions such as temperature 150℃ for the upper part / 100℃ for the lower part, pressure 0.3MPa, and time 1 second. The bag is filled with 200ml of water and 180ml of air, and sealed with an instant sealer. 10 bags of the produced gas-containing packaging are boiled at 95℃×30 minutes, and the number of broken bags is counted after the boiling treatment, and evaluated according to the following standards. In practice, an evaluation of "○" or "◎" is expected.

[0277] (Evaluation Criteria)

[0278] ◎…Very good (no bag damage)

[0279] ○… Slightly better (1 bag was broken in 10 bags)

[0280] △…slightly worse (2 to 4 bags were broken out of 10)

[0281] ×…Poor (more than 5 bags were broken out of 10)

[0282] [Table 1]

[0283]

[0284] [Table 2]

[0285]

[0286] As can be clearly seen from the results of Tables 1 to 2, in Examples 1 to 10, the polyurethane having a silanol group is included in the primer layer of the easy-adhesive polyamide film in an appropriate formulation, and the transparency is excellent, the unevenness in the dot area of ​​halftone printing is small, and the adhesion is also excellent. In addition, the laminated body of the laminated film using the easy-adhesive polyamide film of Examples 1 to 9 has a good lamination strength (X) in normal water, and the ratio (Y / X) of the lamination strength (Y) in water after hot water treatment to the lamination strength (X) in normal water is 0.9 or more, and there are samples with a lamination strength of 1.0 or more (i.e., the lamination strength after treatment is greater than that before treatment), and the gas boiling test is also good.

[0287] In Comparative Examples 1, 2, 5, 9, 10, and 12, the primer layer of the easily adhesive polyamide film did not contain a polyurethane having a silanol group, and although there was no problem in halftone printing, the adhesion was deteriorated.

[0288] Comparative Examples 3 and 4 are films in which the primer layer of the easily adhesive polyamide film does not contain polyurethane having a silanol group. However, the haze value becomes high although there is no problem in the adhesion property by increasing the amount of the lubricant added.

[0289] In Comparative Examples 6 to 8 and 19, the primer layer for easily bonding the polyamide film was composed only of a polyurethane resin having a silanol group, but the dot area ratio of halftone printing became less than 0.8, and deterioration of the printed appearance was observed.

[0290] In Comparative Examples 13 to 15, a crosslinking agent having a crosslinking structure other than a silanol group was added to the primer layer of the easy-adhesive polyamide film, so that local unevenness of the surface was generated starting from the crosslinking point during the drying and stretching process of the coating film, and the dot area ratio after halftone printing was less than 0.8, and deterioration of the printed appearance was observed. In addition, the number of broken bags in the gas boiling test was slightly large.

[0291] In Comparative Example 16, although the primer layer for easily bonding a polyamide film is composed of a polyurethane resin having a silanol group and a polyurethane resin having no silanol group, the polyurethane resin having no silanol group has a low glass transition temperature and poor blocking resistance.

[0292] Since Comparative Example 17 is a polyamide film without a primer layer, although the blocking resistance and halftone printing are good, the lamination strength is low and the number of broken bags in the gas boiling test is large.

Claims

1. An easy-to-bond polyamide film, characterized in that: The polyamide film is a polyamide substrate film having a primer layer formed on at least one surface thereof. (1) the primer layer comprises a polyurethane resin A having no silanol group and a polyurethane resin B having a silanol group, (2) The polyurethane resin A and the polyurethane resin B have different glass transition temperatures Tg.

2. The easy-adhesion polyamide film according to claim 1, wherein The glass transition temperature Tg of the polyurethane resin A is in the range of 5°C to 50°C. The polyurethane resin B has a glass transition temperature Tg in the range of 60° C. or higher.

3. The easy-adhesion polyamide film according to claim 1, wherein When the total amount of the polyurethane resin A and the polyurethane resin B is 100 parts by mass, the polyurethane resin A is 25 to 80 parts by mass, and the polyurethane resin B is 20 to 75 parts by mass.

4. The easy-adhesion polyamide film according to claim 1, wherein The film elongation of the polyurethane resin A is 300% or more and the tensile strength is 20 MPa to 50 MPa. The film elongation of the polyurethane resin B is 200% or more and the tensile strength is 40 MPa to 60 MPa.

5. The easy-adhesion polyamide film according to claim 1, wherein The 2.5 mm diameter of the 50% gradation portion of the halftone printing printed on the primer layer was measured at any 10 locations in the TD direction of the printed film. 2 When the length of the area of ​​300 dots within the image is measured, the ratio of the smallest to the largest area, that is, the average value of the 20 dots with the smallest area / the average value of the 20 dots with the largest area, is in the range of 0.8 to 1.

6. The easy-adhesion polyamide film according to claim 1, wherein The primer layers were stacked on each other, a load of 10 kg / cm was applied, and the adhesion strength after one week in an environment of 40°C was 40 g / 15 mm or less. The easily adhesive polyamide film according to claim 1 , which has a haze of 8% or less. The easily adhesive polyamide film according to claim 1 , which is a biaxially stretched film.

9. A laminate, wherein: On the primer layer of the easily adhesive polyamide film according to any one of claims 1 to 8, at least a laminated adhesive layer and a heat seal layer are laminated in this order directly or via a printed layer.

10. A method for producing an easy-to-bond polyamide film, comprising: (1) a step of applying an aqueous coating agent comprising a polyurethane resin A having no silanol group and a polyurethane resin B having a silanol group onto at least one surface of an unstretched polyamide substrate film; and (2) A step of biaxially stretching the polyamide film coated with the aqueous coating agent and then heat-treating it.

11. The manufacturing method according to claim 10, wherein: The biaxial stretching is simultaneous biaxial stretching.

12. A method for producing an easy-to-bond polyamide film, comprising: (1) a step of uniaxially stretching an unstretched polyamide substrate film in a first direction; (2) a step of applying an aqueous coating agent comprising a polyurethane resin A having no silanol group and a polyurethane resin B having a silanol group onto at least one surface of a uniaxially stretched polyamide substrate film; and (3) A step of uniaxially stretching the polyamide base film coated with the aqueous coating agent in a second direction perpendicular to the first direction and then heat-treating the film.

Citation Information

Patent Citations

  • Highly adhesive polyamide film and production method therefor

    WO2010110282A1